Penerapan Metode Outdoor Learning Untuk Meningkatkan Aktivitas Dan Prestasi Belajar Siswa Pada Pembelajaran PKN Di Kelas Va SD Negeri 51 Kota Bengkulu - Neri Eltiyani; Syahril Yusuf; Neza Agusdianita (JURIDIKDAS, 2020)
This study aims to increase the activity and student learning achievement by applying the outdoor learning method in class VA SD Negeri 51  Bengkulu. This type of research is classroom action research. The subjects of this study were class VA students at SD Negeri 51 Bengkulu. The research procedure is in the form of  cycles II. The research instruments were in the form of student observation sheets and test sheets. The test data analysis technique uses the average value formula and the percentage of classical learning completeness. The results analysis of student activities obtained in the cycle I obtained an average of 31.25 with good categories increased in the cycle II obtained an average of 39.75 with a very good category. While for student learning achievement in the cycle I with an average of 74.09 and classical learning completeness 63.63% increased in the cycle II with an average of 82.04 and classical learning completeness of 90.90%. The conclusion of this study is that the application of outdoor learning methods can improve the activities and student learning achievement in Civics learning in the VA class of SD Negeri 51 Bengkulu